Influence of phi mesons on negative kaons in Ni + Ni collisions at 1.91A GeV beam energy - Piasecki, Krzysztof; Herrmann, Norbert; Deppner, Ingo Martin; Liu, Jian-Li; Reischl, Alexander Antonius; Wisniewski, Krzysztof; Zinyuk, Victoria (Physical review. C, Nuclear physics, 2015)
ϕ and K− mesons from Ni+Ni collisions at the beam energy of 1.91A GeV have been measured by the FOPI spectrometer, with a trigger selecting central and semicentral events amounting to 52% of the total cross section. The phase-space distributions, and the total yield of K−, as well as the kinetic energy distribution and the total yield of ϕ mesons are presented. The ϕ/ K− ratio is found to be 0.44±0.07(stat)+0.16−0.10(syst), meaning that about 22% of K− mesons originate from the decays of ϕ mesons, occurring mostly in vacuum. The inverse slopes of direct kaons are up to about 15 MeV larger than the ones extracted within the one-source model, signaling that a considerable share of gap between the slopes of K+ and K− could be explained by the contribution of ϕ mesons to negative kaons.